International monetary policy : Bretton Woods and after - Scammell, W. M. (London: Macmillan; New York, St. Martin's Press, 1957)
The book contains a careful exposition of the theory of balance of payments adjustments and policy. It also follows its predecessors in its careful analysis of the Bretton Woods system and an examination of its functioning. It also focused on the problems facing the architects of the postwar monetary system and the nature of the Bretton Woods agreements, existing pattern of international payments.
Includes index
Includes bibliographical references.
usc 16/04/18; 25/09/18
Loans
Keywords: Balance of payments; Foreign exchange; International finance; Monetary policy; Currency question